Study on the Changing Rules of Silty Clay’s Pore Structure under Freeze-Thaw Cycles - Zongfang Chen; Huie Chen; Jinfeng Li; Hui Li; Wenliang Ma (Advances in Civil Engineering)
For engineering construction in seasonally frozen regions, when the soil below the frost depth without freeze-thaw effect was exposed or reclaimed after excavation, long-term freeze-thaw will change soil skeleton and porous characteristics, thereby leading to the deterioration of soil engineering properties. This study focused on seasonally frozen silty clay from Changchun, China, and conducted different freeze-thaw cyclic tests on remoulded soil samples, during which both freezing temperature and the number of freeze-thaw cycles were varied. The related data of pore structures under different test conditions were acquired through mercury injection porosimetry (MIP) tests, and the effects of the number of freeze-thaw cycles and freezing temperature on the change of the soil’s pore structure were investigated in detail in combination with fractal theory. The variation rules of pores in the soil after freeze-thaw cycles were investigated from a microperspective so as to essentially analyze the mechanism of the deteriorating effect of freeze-thaw on a soil’s engineering properties.